2017
DOI: 10.1039/c6ra25580a
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible, optically transparent, patterned, and flexible electrodes and radio-frequency antennas prepared from silk protein and silver nanowire networks

Abstract: We demonstrated biocompatible, optically transparent and flexible electrodes by embedding AgNWs just below the surface of the silk fibroin film.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…In addition, there are reports on electrodes that use highly biocompatible materials such as poly-vinyl-alcohol (PVA), [18,21] gels, [22] and silk fibroin for biocompatibility. [23,24] Biocompatibility is especially important when considering the wearing of electrodes on patients with skin diseases. Clinicians evaluate it using methods such as the patch test and histological staining procedures.…”
Section: Doi: 101002/adhm202001322mentioning
confidence: 99%
“…In addition, there are reports on electrodes that use highly biocompatible materials such as poly-vinyl-alcohol (PVA), [18,21] gels, [22] and silk fibroin for biocompatibility. [23,24] Biocompatibility is especially important when considering the wearing of electrodes on patients with skin diseases. Clinicians evaluate it using methods such as the patch test and histological staining procedures.…”
Section: Doi: 101002/adhm202001322mentioning
confidence: 99%
“…40 Min et al demonstrated that patterned Ag NW on a SF substrate acts as a transparent resistor and a radiofrequency antenna for food sensors. 41 Qi et al reported that Ag NW and SF composite lms have excellent transmittance and conductivity and can be used as exible interconnectors. Although several applications of Ag NW-SF compositions or Ag NW-coated SF substrates, such as bacteria sensors, photonics, electronic devices, food sensors, actuators, therapeutics, and energy harvesting devices have been suggested, their use as electrodes for wearable transparent and exible heaters (TFHs) has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, many approaches used to prepare silver nanowires networks have been presented including vacuum filtration, the drop-cast method, Meyer rod coating, and the transfer-printing technique [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. However, it is very difficult to achieve a high quality film with low sheet resistance, high optical transmittance, and good adhesion between the nanowires and substrate surface at the same time.…”
Section: Introductionmentioning
confidence: 99%